A review on knowledge audit process - Ahmad Shukor, Nur Syufiza (2013)
Knowledge audit output helps organizations to make recommendation of KM strategy which later can be used for better managing the knowledge. This paper reviews literature on knowledge audit process with the aim to understand the process, the data gathering techniques employed and the roles of knowledge audit. It aims to report the research gaps and propose directions for future research in this domain. A comprehensive three-stage method for extracting, analyzing and reporting the literature-based findings was applied in analyzing the literature survey. The literature survey is based on a search for the keywords “knowledge audit”, “knowledge audit process”, “knowledge audit output” and “knowledge audit roles”, first on the ISI Web of Knowledge online database, followed by Association of Information Systems basket of top journals and other reputable literatures. The paper concludes with an understanding on how knowledge audit is conducted, the data gathering techniques used and its contributions to the organization. However no literature was found on knowledge audit practices for inter-organization. Future research on how knowledge audit could be extended for inter-organization is suggested at the end of the paper. However, this paper only covers literature that discussed in depth the knowledge audit process published in certain journals. Never the less, it is believed that the findings provide a valuable understanding of the current situation in this research field.